Intra-cluster synchronization scheme for femtocell network - Kamrul Hasan, Mohammad; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Islam, Shayla; Saeed, Rashid A. (IEEE, 2012)
With the intention of establishing the connectivity between the femtocell and the core network, it is essential to use public network that ultimately creates several challenges for the operators. Therefore, Synchronization is considered corner stone and has become one of the most significant issues in femtocellular networks to ensure a tolerable carrier offset as well as support received signals in order to reduce multi-access interference. In this paper, one potential synchronization schemes for femtocell are presented which is intra-cluster synchronization scheme. An intra-cluster synchronization scheme is proposed to minimize the clock offset for the better synchronization accuracy. The analytical result shows that the proposed scheme can achieve synchronization accuracy up to 90% higher than the existing MS-assisted schemes.